2020
DOI: 10.1016/j.heliyon.2020.e04610
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional titanium dioxide nanoparticles biofabricated via phytosynthetic route using extracts of Cola nitida: antimicrobial, dye degradation, antioxidant and anticoagulant activities

Abstract: First study of phytosynthesis of TiO 2 NPs using the leaf (KL), pod (KP), seed (KS) and seed shell (KSS) extracts of kola nut tree ( Cola nitida ) is herein reported. The TiO 2 NPs were characterized and evaluated for their antimicrobial, dye degradation, antioxidant and anticoagulant activities. The nearly spherical-shaped particles had λmax of 272.5–275.0 nm with size range of 25.00–191.41 nm. FTIR analysis displayed prominent peaks at 3446… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…TiO 2 -NPs have been used in the food industry since 1996 when the US Food and Drug Administration approved it as a food supplement [17]. TiO 2 -NPs are also used for electrostatic properties in terms of electrostatic potentials and ion distributions [18] for dye-degrading activities, H 2 O 2 scavenging, and anticoagulant activities [19] to enhance the glasses' radiation protection properties along with bioactive glasses [20] as nanocarriers for drug delivery [21] and as a nano-drug for treating diseases [22]. The idea of agents for two modes of therapy enhancement and image contrast is one field that remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 -NPs have been used in the food industry since 1996 when the US Food and Drug Administration approved it as a food supplement [17]. TiO 2 -NPs are also used for electrostatic properties in terms of electrostatic potentials and ion distributions [18] for dye-degrading activities, H 2 O 2 scavenging, and anticoagulant activities [19] to enhance the glasses' radiation protection properties along with bioactive glasses [20] as nanocarriers for drug delivery [21] and as a nano-drug for treating diseases [22]. The idea of agents for two modes of therapy enhancement and image contrast is one field that remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was observed that these bioinspired titanium oxide nanoparticles maintained the morphology of red blood cells. 220 Apart from the plants showing anti-coagulation activities, several other organisms (like Hirudinea) exhibit excellent anti-coagulation properties, and therefore can be utilized to synthesize various metal and metal oxide nanoparticles to exhibit anti-coagulation activity.…”
Section: Applicationsmentioning
confidence: 99%
“…In addition to curtailing MDR strains, metal nanoparticles also possess several other beneficial biomedical attributes. These include antioxidant [ 167 , 168 , 169 , 170 , 171 ], anticoagulant [ 4 , 172 , 173 , 174 , 175 ], thrombolytic [ 4 , 172 , 173 ], anti-inflammatory [ 176 , 177 ], anti-diabetic [ 178 , 179 , 180 ], anti-cancer [ 179 , 180 , 181 , 182 , 183 ] and wound healing [ 184 , 185 ] properties. In translational studies, nanoparticle-based antibiotic delivery systems can be created by coating nanoparticles on implanted devices, wound dressings, bone cement and dental materials [ 186 , 187 , 188 , 189 , 190 ] to kill germs and prevent infections.…”
Section: Deployment Of Nanoparticles Against Harmful and Multi-drug R...mentioning
confidence: 99%